PENGARUH NAUNGAN TERHADAP PERUBAHAN IKLIM MIKRO PADA BUDIDAYA TANAMAN TEMBAKAU RAKYAT - Sudaryono, Sudaryono (Jurnal Teknologi Lingkungan, 2004)
Observed from context of the physical environment, especially micro climate, to get tobacco leaf with good quality, hence have to fulfill any conditions : dampness of air (about 60%-80%), mean of rain-fall per month more or less 175 mm, air temperature range from (21-33)°C, and irradiating intensity of the sun (about 61- 69)%. For many area the conditions difficult to fulfilll because the situation of microclimate is sometime uncertainty.Pursuant to the problem, have been conducted an experiment to improve the life environment at the tobacco crop with manipulating physical environment (micro climate) by growing the tobacco crop under closed shade.Through the environmental engineering of physical, heve been obtained a micro climate element like: temperature, dampness of air, photosynthesis, sun radiation, speed of wind, which yielded have come near conditions on grow to tobacco crop, hence may be expected will be obtained a better tobacco production and quality.